Alterations of microrna expression patterns in human cervical carcinoma cells (CA SKI) towards 1'S-1'-acetoxychavicol acetate (ACA) and cisplatin (CDDP) / Phuah Neoh Hun - Phuah, Neoh Hun (2012)
The main aims of this study were to investigate the combined effects of a natural compound 1’S-1’-acetoxychavicol acetate (ACA) with cisplatin (CDDP) on human cervical carcinoma cells Ca Ski, and to identify microRNAs (miRNAs) asscociated with response towards ACA and/or CDDP. Data obtained from MTT cell viability assays indicated that both ACA and CDDP induced dose- and time-dependent cytotoxicity on Ca Ski cells when used as a standalone agent. The in vitro studies also demonstrated that ACA potentiates the cytotoxic effects of CDDP when used in combination through synergistic interactions. The miRNA microarray was used to identify global miRNA expression profiles on Ca Ski cells following administration of ACA and/or CDDP, and it was found that 25 miRNAs were differentially expressed in response towards ACA and/or CDDP with markedly different pattern of miRNA expressions between different treatment regimens. Three promising miRNA candidates (hsa-miR-138, hsa-miR-210 and hsa-miR-744) which exhibited the highest fold-change in combination chemotherapy and whose expressions were among those validated by qRT-PCR, were selected for bioinformatic analyses. The hypothetical pathway model comprising interaction between candidate miRNAs with their putative target genes indicated that the cytotoxic effects induced by ACA in combination with CDDP may be regulated by miRNA expression. Therefore, our study provides a platform for potential therapeutic approaches in chemotherapy, whereby miRNA expression can be exploited to further improve efficacy in combination chemotherapy.